Fabrication and Characterization of Carboxymethyl Starch/Poly(l-Lactide) Acid/β-Tricalcium Phosphate Composite Nanofibers via Electrospinning - Yusof, Mohd Reusmaazran; Shamsudin, Roslinda; Zakaria, Sarani; Abdul Hamid, Muhammad Azmi; Yalcinkaya, Fatma; Abdullah, Yusof; Yacob, Norzita (Polymers, 2019)
A natural polymer of carboxymethyl starch (CMS) was used in combination with the inorganic mineral of β-Tricalcium Phosphate (β-TCP) and Poly l-lactide (PLLA) to prepare composite nanofibers with the potential to be used as a biomedical membrane. β-TCP contents varied in the range of 0.25% to 1% in the composition of PLLA and CMS. A mixed composition of these organic and inorganic materials was electro-spun to produce composite nanofibers. Morphological investigation indicated that smooth and uniform nanofibers could be produced via this technique. The average of the nanofiber diameters was slightly increased from 190 to 265 nm with the β-TCP content but some agglomeration of particles began to impede in the fiber at a higher content of β-TCP. It was observed that the fibers were damaged at a higher content of β-TCP nanoparticles. With the presence of higher β-TCP, the wettability of the PLLA was also improved, as indicated by the water contact angle measurement from 127.3° to 118°. The crystallization in the composite decreased, as shown in the changes in glass transition (Tg) and melting temperature (Tm) by differential scanning calorimeter (DSC) and X-ray diffraction analysis. Increases in β-TCP contributed to weaker mechanical strength, from 8.5 to 5.7 MPa, due to imperfect fiber structure.
Keywords: β-tricalcium phosphate (β-TCP); electrospinning; carboxymethyl starch (CMS); nanofibers; poly l-lactide (PLLA)